Waste Management Education to Enhance Vendors' Awareness for a Clean and Healthy Kebon Roek Market in Mataram City: Edukasi Pengelolaan Sampah untuk Meningkatkan Kesadaran Pedagang dalam Mewujudkan Pasar Kebon Roek yang Bersih dan Sehat di Kota Mataram - Baiq Ratih Widatari; Dea Kiki Amanda; Helmi Maulia Nara Hasanah; Husnul Mawalia; Lalu Annual Aji Sukma; Miqrazul Azahra; Nurfitriningsih; Sri Maulina Ulfa; Endang Kurinawati (Yayasan Siti Widhatul Faeha, 2026)
Traditional markets generate considerable waste that requires proper management to maintain environmental cleanliness and public health. Initial observations at Kebon Roek Market in Mataram City identified several environmental problems, including scattered waste, inadequate waste disposal facilities, poor drainage, and limited awareness among vendors of proper waste management. This community service program aimed to enhance vendors' awareness and participation in waste management to support a clean and healthy market environment. The program targeted vendors, market managers, and community members conducting activities in the market and was implemented using the Participatory Learning and Action (PLA) approach through field observations, waste management education, socialization, interactive discussions, and practical mentoring on waste segregation. Program evaluation was conducted qualitatively through observations of participants' involvement, discussion outcomes, and changes in participants' understanding following the activities. The results showed improved understanding among participants regarding waste segregation, environmental sanitation, and the importance of maintaining market cleanliness. The activities also encouraged greater awareness and collective commitment among vendors and market managers to properly manage waste and maintain a cleaner, healthier, and more sustainable market environment. These findings demonstrate that educational and participatory approaches are effective in strengthening environmental awareness and promoting sustainable waste management practices in traditional markets.